Ontological Principles of Aesthetic Theory by L. Karsavin - Tamošiūnienė, Inesa (Problemos, 1982)
L. Karsavin, a representative of Russian religious idealism at the beginning of this century, who worked in Lithuania for a long time, solves ethical problems basing on the mystical principle of “universal unity”. Much attention is given to the realization of the above principle, i.e., to the problem of interrelation of moral ideal (the Good) and ethical practice (the Evil). The contradiction between the Good and the Evil is to be eliminated by “universal unity”. It is shown in the article that the mystifications of social, including moral, relations by L. Karsavin leads to an actual conformity of Man to the Evil existing in society.